Sensitivity and Specificity of the Ohio State University Traumatic Brain Injury Identification Method to Neuropsychological Impairment. (June 2018) - Glover, Nicole; Gorgens , Kim; Lehto, Marybeth; Meyer, Laura; Dettmer, Judy; Gafford, Jennifer
Offenders in justice system settings have high rates of traumatic brain injury (TBI) in comparison with the general population. Consequently, justice systems are using screening tools to identify and manage these individuals. Currently, that includes screening for TBI history and gross cognitive impairment. The present study attempted to determine whether the modified Ohio State University Traumatic Brain Injury Identification Method (OSU TBI-ID) was predictive of ongoing cognitive impairment as measured by the Automated Neuropsychological Assessment Metrics (ANAM) Core Battery. If so, the OSU TBI-ID could be used as a stand-alone measure of TBI history and impairment. This study had 223 participants (male = 160, female = 62). Sensitivity and specificity results revealed poor (.65) to very poor (.36) estimates for all OSU TBI-ID indices across all ANAM subtests. This study suggests that screening for lifetime history of TBI does not identify cognitive impairment. Implications for screening policy and future research are discussed.